PELATIHAN BAHASA INGGRIS INTENSIF BERORIENTASI KERJA BAGI REMAJA PUTUS SEKOLAH DI DESA LABUAN TERENG, LEMBAR KABUPATEN LOMBOK BARAT - NUSA TENGGARA BARAT - Ariyani, Etika; Jannah, Miftahul (Bajang Institute, 2025)
Mastering English skills for work oriented very important because it can improve opportunities to get better jobs especially for teenagers dropping out of school in Labuan Tereng village, West Lombok - - West Nusa Tenggara Province (NTB). The purpose of this community service program was to equip english skills for dropping out teenagers intensively in order to get better jobs. This program was held for three months from August to October 2025, twice a week with 90 minutes time allocation for every session. This training followed by 12 active participants , methods which applied are lecturing, small group discussion , jigsaw, picture- picture and role play to improve participants knowledge and skill which they need based on the participant characteristics. Social media such as youtube, tik tok and instagram used to improve vocabulary enrichment and grammar. The result of this community service program shown that there is significant improvement of participants performances which the result of pre - cycle 50.08 %, the result of first cycle 62.16 % then increased significantly to 76.33 % at second cycle. Participants improvement indicator fulfilled 70 % , the participants looks enjoy, happy and enthusiastic followed this program. Based on those finding, we can concluded that methods which applied in this community service program effective to improved participants performances significantly